Development of grammatical activities In a digital learning environment - Samarina, V.; Shamrai, О.; Самаріна, В. В.; Шамрай, О. В.; Самарина, В. В.; Шамрай, Е. В. (Харьковский национальный автомобильно-дорожный университет, 2018)
The article aims at highlighting the usefulness of grammatical explanations when associated with prototypes of actual productions of utterances. At the same time, textual functions of grammatical markers will be associated to complete the analysis of the textual structure.
Розвиток граматичної діяльності в цифровому середовищі навчання
Развитие грамматической деятельности в цифровой среде обучения
Keywords: discourse analysis; grammar; ICT; foreign language; cognition; аналіз дискурсу; граматика; ІКТ іноземна мова; пізнання; анализ дискурса; грамматика; ИКТ; иностранный язык; познание; 81’243=811.111:007